Über den Tod - Ps.-Platon (Mohr Siebeck, 2012)
In this volume, the pseudo-Platonic dialogue »Axiochus« is integrated for the first time philologically and philosophically into the context of the so-called Middle Platonism and the intense reception of this »ars moriendi« in the early modern period is examined.
PublicationDate: 20120412
Keywords: Hellenismus -- Komposition und Redaktion -- (Pseudo)-Platon -- Axiochos -- Mittelplatonismus -- ars moriendi -- Studienliteratur -- Editionen, Textausgaben -- Antike -- Antike Philosophie -- Antike Religionsgeschichte -- Alte Geschichte -- Ethik -- Anthropologie -- Lehrbücher -- Ethics -- Studienliteratur - Theologie -- Textbooks - Theology -- Editionen, Textausgaben - Theologie -- Array